Héctor Abad Gómez como educador popular. Un acercamiento a su vida, obra y discursos (2017)
ABSTRACT: To propose Hector Abad Gomez as the people's healthcare educator by approaching his life and his work. Methodology: This historical pedagogical research conducted a critical reading of 173 written by Abad Gómez or about his life, selecting 70 of them. Discussion: Hector Abad Gomez recreated in his works Paulo Freire's tenets regarding what it is to be a people's educator, integrating in his life principles and values like ethical-political coherence, the transformation of reality and direct Community work. These three items make up one of his greatest proposals: Rural Healthcare promoters. Conclusions: Hector Abad’s work with promoters, his actions as a human rights advocate and his life as an educator rank him as one of the first people's Educators in Colombia, where Healthcare & Life appear as scenarios for the vindication of human dignity.